KOMPETENSI KEPRIBADIAN KONSELOR DALAM PELAKSANAAN BIMBINGAN DAN KONSELING ISLAM - Riem Malini Pane (IAIN Padangsidimpuan, 2016)
Counselors are experts / professionals who have particular expertise in the field ofguidance and counseling competence in terms of personality, knowledge, skills andexperience . Qualified academic counselors in the educational unit on the path ofeducation is S-1 in the field of guidance and counseling and counselor EducatedProfessionals. Competence is the counselor's personality factor is crucial in theimplementation of counseling. Counselors are required to facilitate the development ofpersonal competence and is responsible for the guidance of the Qur'an and religiousmaturity.